73 HYPERTENSION-INDUCED CONTRACTILE DYSFUNCTION, LEFT VENTRICULAR HYPERTROPHY, AND DOWN-REGULATION OF MITOCHONDRIAL METABOLIC ENZYME ACTIVITY ARE ATTENUATED BY HIGH-FAT/LOW-CARBOHYDRATE FEEDING. (1st March 2006) - Okere, I. C.; Chess, D. J.; McElfresh, T. A.; Young, M. E.; Ernsberger, P.; Hoit, B. D.; Chandler, M. P.; Stanley, W. C.
Abstract : Cardiac hypertrophy and heart failure are characterized by increased expression of atria natriuretic peptide (ANP), a decrease in the activity of fatty acid oxidation (FAO) enzymes, impaired mitochondrial respiration, and LV remodeling and systolic dysfunction. Fatty acids up-regulates the expression of FAO enzymes via activation of peroxisomal proliferator activator receptors. We hypothesized that a high-fat diet would prevent down-regulation of FAO enzymes activity and slow development of cardiac dysfunction in a model of hypertension-induced hypertrophic cardiomyopathy. Three groups ( n = 10) of 11-week-old male Dahl salt-sensitive rats were fed (1) low-fat/low-salt rodent chow (10% calories from fat) (LF-LS), (2) low-fat/high-salt chow (6% NaCl) (LF-HS), or a high-fat/high-salt diet (60% calories from fat, 6% NaCl) (HF-HS) for 12 weeks. Tail cuff blood pressure and echocardiographic assessment of LV dimensions and function were performed before initiation of diets and after 11 weeks on diets. Myocardial activities of citrate synthase (CS) and medium chain acyl dehydrogenase (MCAD) activities were measured, and the mRNA expressions for ANP was measured. Results: There were no differences in body weight among groups. Salt feeding caused similar elevations in systolic blood pressure in LF-HS and HF-HS groups (< 190 mm Hg compared to 120 mm Hg in LF-LS). LV mass was increased in LF-HS (1.30 ± 0.06 g) compared to LF-LS (0.90 ± 0.02 g). Hypertension down-regulated CS and MCAD activities in the LF-HS group but not in the HF-HS group. LV end-diastolic volume and ANP expression were elevated and fractional shortening reduced in HS-LF compared to LS-LF. The HF-HS group had reduced LV hypertrophy (1.16 ± 0.05 g) and ANF expression and showed no LV remodeling or systolic dysfunction compared to LF/HS fed rats. Conclusion: High-fat diet prevented the down-regulation of the activity of metabolic enzymes and preserved contractile function and LV chamber dimensions in this model of hypertrophic cardiomyopathy.